Obtención de una bebida fermentada de naranja (Citrus sinensis) aplicando la enzima peptinasa (PEC-600) como clarificante - Remache Castillo, Haideé Estefanía (2015)
In this research work was the obtaining of a fermented beverage of Orange (Citrus sinensis) using the enzyme peptinasa (PEC-600) as clearer. In the fermented beverage of Orange, the main problem is turbidity attribute that produces consumer rejection. In this sense the general objective of this research was to establish and determine which of the varieties of National orange or Tangelo, dry or wine yeast types and concentrations of the enzyme peptinasa (PEC-600) at 0.2% and 0.4% causes a better effect at the stage of clarification, resulting in a clean turbidity product. The raw material was obtained from two farms in the Cantón Valencia province of Los Ríos (National orange) and in the parish of Moraspungo province of Cotopaxi (Tangelo orange). Free of any impurities selected oranges was used for the manufacture of the product, was washing and disinfection of the fruit then make the extraction of the juice which are fitted out appropriately. During fifteen days the fermentation in which was made peptolítica to 450C enzyme was added after this period of time. Subsequently to it maturation it left at rest for two months in a place in storage at room temperature conditions. The experimental design used was an arrangement block Factorial completely randomized to the A*B*C with the application of analysis of variance for each study variable, determined 8 treatments with 3 replicates giving a total of 24 experimental units. Chemical analysis was performed as: pH, total acidity, Brix degrees and alcoholic. As best treatment was establish a0b0c0 (National Orange*concentrations of 0.2% peptinasa*dry yeast) obtaining a fermented drink sweet, who presented the best xix